High-power lithium iron phosphate battery and preparation method thereof

By optimizing the material structure of the positive and negative electrodes, as well as the design of the electrolyte and separator, the problem of insufficient high-power discharge capability of lithium-ion batteries has been solved, achieving long cycle life and high reliability of high-power lithium iron phosphate batteries.

CN121307150APending Publication Date: 2026-01-09JIANGSU HIGHSTAR BATTERY MFG CO LTD +3
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511706412.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-20
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

The discharge rate of existing lithium-ion batteries is mostly limited to 2C to 6C, which cannot meet the requirements of UPS systems for instantaneous high-power discharge, becoming a key bottleneck to improving the power density of UPS systems.

Method used

By optimizing the material structure of the positive and negative electrodes, including using transition metal-doped lithium iron phosphate cores and ultrathin carbon layers to construct a three-dimensional conductive network, combined with optimized electrolyte and separator design, a stable SEI/CEI film is formed, reducing interface impedance and electronic impedance, and improving the lithium-ion insertion/extraction rate.

Benefits of technology

It achieves that the capacity retention rate of high-power lithium iron phosphate batteries can still be maintained at over 80% after 500 cycles of 1C charging/10C discharging, with longer cycle life and high reliability, meeting the high-power discharge requirements of UPS systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121307150A_ABST
    Figure CN121307150A_ABST
Patent Text Reader

Abstract

The invention discloses a high-power lithium iron phosphate battery and a preparation method thereof. The high-power lithium iron phosphate battery comprises a positive plate, a negative plate, a diaphragm and electrolyte. The positive plate comprises a positive material layer and a positive current collector; the negative plate comprises a negative electrode material layer and a negative electrode current collector; the diaphragm is coated with an adhesive layer composed of ceramic and polyvinylidene fluoride, and the porosity of the diaphragm is 45%-50%; the electrolyte comprises a lithium salt, an organic solvent and an additive, and the mass ratio of the lithium salt to the organic solvent to the additive is (13-18): (75-80): (3-8). By optimizing the positive plate, the negative plate, the diaphragm and the electrolyte, the prepared high-power lithium iron phosphate battery has high reliability, long cycle life and wide temperature range under high-power discharge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, and in particular to a high-power lithium iron phosphate battery and its preparation method. Background Technology

[0002] A UPS (Uninterruptible Power Supply) is a system that connects a battery to a main unit and uses inverters and other circuit modules to convert direct current (DC) to AC power. Its core function is to provide stable and uninterrupted power to computer systems, network equipment, and other critical loads when AC power is abnormal or interrupted, ensuring their stable operation and protecting hardware and software from damage.

[0003] Lithium-ion batteries, with their high energy density, long cycle life, high safety, and excellent environmental adaptability, have become an important choice for data center backup power supplies (UPS). With the rapid development of technologies such as artificial intelligence, the computing power density of data centers and computing centers continues to rise, placing more stringent demands on UPS systems, especially their core energy storage units, in terms of instantaneous high-power discharge capabilities. However, the discharge rates of most mainstream lithium-ion batteries on the market are currently limited to 2C–6C, which has become a key bottleneck in improving the power density of UPS systems. Summary of the Invention

[0004] This invention aims to at least solve one of the technical problems existing in the prior art. To this end, this invention provides a high-power lithium iron phosphate battery and its preparation method, which, through optimization of the positive electrode, negative electrode, and structural components, prepares a high-power lithium iron phosphate battery with excellent rate discharge performance.

[0005] A high-power lithium iron phosphate battery according to a first aspect embodiment of the present invention includes a positive electrode, a negative electrode, a separator, and an electrolyte; The positive electrode sheet includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The positive electrode material layer includes carbon-coated lithium iron phosphate positive electrode material, a conductive agent, and polyvinylidene fluoride (PVDF). The carbon-coated lithium iron phosphate positive electrode material consists of a transition metal-doped lithium iron phosphate core and a carbon layer coating the surface of the transition metal-doped lithium iron phosphate core. The transition metal is at least one of vanadium and titanium. The median particle size of the transition metal-doped lithium iron phosphate core is 0.2-2 μm. The carbon layer is obtained by solid-state sintering of at least one carbon source, glucose and sucrose, with at least one conductive material, graphene and carbon nanotubes, and has a thickness of 0.1-0.3 μm. The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The negative electrode material layer includes carbon-coated graphite negative electrode material, a conductive agent, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR). The carbon-coated graphite negative electrode material includes graphite particles and a soft carbon layer coated on the surface of the graphite particles. The median particle size of the graphite particles is 6-10 μm, and the soft carbon layer is obtained by pyrolysis of a liquid-phase carbon source and has a thickness of 0.2-1 μm. The diaphragm includes a base membrane and an adhesive layer composed of ceramic and polyvinylidene fluoride (PVDF) coated on the upper and lower surfaces of the base membrane. The base membrane is at least one of polypropylene and polyethylene, and the porosity of the diaphragm is 45% to 50%. The electrolyte comprises lithium salt, organic solvent and additives, wherein the mass ratio of the lithium salt, the organic solvent and the additives is 13-18:75-80:3-8.

[0006] According to some embodiments of the present invention, in the cathode material layer, the mass ratio of the carbon-coated lithium iron phosphate cathode material, the conductive agent and the polyvinylidene fluoride (PVDF) is 92-97:1-4:2-4.

[0007] According to some embodiments of the present invention, the positive current collector comprises an aluminum foil and a carbon coating coated on the upper and lower surfaces of the aluminum foil. The carbon coating comprises conductive carbon black, carbon nanotubes, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR), and the dry weight areal density of the carbon coating is 0.8-1.5 g / m³. 2 .

[0008] According to some embodiments of the present invention, in the negative electrode material layer, the mass ratio of the carbon-coated graphite negative electrode material, the conductive agent, the sodium carboxymethyl cellulose (CMC) and the styrene-butadiene rubber (SBR) is 92-97:0.5-2.5:1-2.5:1.5-3.

[0009] According to some embodiments of the present invention, the negative electrode current collector comprises a copper foil and a carbon coating coated on the upper and lower surfaces of the copper foil. The carbon coating comprises conductive carbon black and carbon nanotubes, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR), and the dry weight areal density of the carbon coating is 0.5-1.2 g / m³. 2 .

[0010] According to some embodiments of the present invention, in the electrolyte, the lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), lithium dioxolane borate (LiBOB), lithium tetrafluoroborate (LiBF4), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI); the organic solvent includes one or more of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), ethyl acetate (EA), and ethyl propionate (EP); the additive includes one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), lithium difluorooxolane borate (LiODFB), ethylene sulfate (DTD), tris(trimethylsilyl) phosphate (TMSP), and lithium difluorophosphate (LiPO2F2).

[0011] According to some embodiments of the present invention, the high-power lithium iron phosphate battery further includes a cover plate and a connecting piece; the cover plate includes an electrode post with a diameter of 18-24 mm; the connecting piece includes a positive electrode connecting piece and a negative electrode connecting piece, the positive electrode connecting piece being an aluminum sheet with a thickness of 1.2-1.5 mm, and the negative electrode connecting piece being a copper or nickel sheet with a thickness of 0.8-1.2 mm.

[0012] A method for preparing a high-power lithium iron phosphate battery according to a second aspect embodiment of the present invention includes the following steps: Preparation of positive electrode sheet: Prepare carbon-coated lithium iron phosphate positive electrode material; mix the carbon-coated lithium iron phosphate positive electrode material, the conductive agent and the polyvinylidene fluoride (PVDF) in an organic solvent at a mass ratio of 92-97:1-4:2-4 to form a uniform positive electrode slurry; uniformly coat the positive electrode slurry onto the positive electrode current collector with a dry weight areal density of 100-170 g / m2; and obtain the positive electrode sheet by drying, rolling and shearing. Preparation of the negative electrode sheet: A carbon-coated graphite negative electrode material is prepared; the carbon-coated graphite negative electrode material, the conductive agent, the sodium carboxymethyl cellulose (CMC), and the styrene-butadiene rubber (SBR) are mixed in deionized water at a mass ratio of 92-97:0.5-2.5:1-2.5:1.5-3 to form a uniform negative electrode slurry. The negative electrode slurry is then prepared with a dry weight single-sided surface density of 50-80 g / m³. 2 The material is uniformly coated onto the negative electrode current collector, and then dried, rolled, and sheared to obtain the negative electrode sheet. Preparation of the diaphragm: The base membrane of the diaphragm is at least one of polypropylene and polyethylene, and an adhesive layer composed of ceramic and polyvinylidene fluoride (PVDF) is coated on the upper and lower surfaces of the base membrane to obtain a diaphragm with a porosity of 45% to 50%; wherein, the coating method includes one of multilayer coating, mixed coating and dot coating.

[0013] Preparation of electrolyte: The lithium salt, the organic solvent and the additive are mixed in a mass ratio of 13-18:75-80:3-8; Pre-processed battery assembly: The positive electrode sheet, the separator, and the negative electrode sheet are sequentially stacked and wound to form a battery cell; one end of the positive and negative electrode connecting pieces is connected to the positive and negative current collectors of the positive and negative electrode sheets using ultrasonic welding technology; the battery cell is placed in an aluminum shell and covered with a cover plate; the other end of the positive and negative electrode connecting pieces is connected to the positive and negative electrode posts of the cover plate using laser welding; the edge of the cover plate is sealed and welded to the edge of the opening of the aluminum shell; baking and drying are performed to obtain the pre-processed battery; Electrolyte injection, formation, sealing and Mylar film assembly: Inject the electrolyte into the casing of the pre-processed battery and bake it in an inert gas atmosphere for 8 to 15 hours; perform formation; seal the injection hole; heat shrink or fit the cut Mylar film onto the outside of the battery aluminum casing.

[0014] According to some embodiments of the present invention, the preparation of carbon-coated lithium iron phosphate cathode material specifically includes the following steps: Lithium source, iron source, phosphorus source, vanadium source and titanium source were selected according to the molar ratio of ions Li + Fe 2+ :PO4 3- V 5+ Ti 4+ =1:1-xy:1:x:y is dissolved in deionized water or dispersed in ethanol, where 0 < x < 0.005 and 0 < y < 0.005; a carbon source and conductive material are added, dispersed to form a uniform slurry, and dried to obtain the precursor; The precursor is pre-sintered at 300-400℃ for 2-5 hours; The pre-sintered precursor is ground into a uniform powder, heated to 600-800℃ under inert gas protection, and held at 600-800℃ for 8-15 hours. After cooling, it is ground and sieved.

[0015] According to some embodiments of the present invention, the preparation of the carbon-coated graphite anode material specifically includes the following steps: Primary granulation: Select at least one of petroleum coke or needle coke, crush and shape it to obtain primary particles with a median particle size of 6-8μm; under inert gas protection, heat the primary particles to 2800-3000℃ and keep them at 2800-3000℃ for more than 3 hours to graphitize them, and obtain graphitized primary particles. Liquid phase carbonization coating and secondary granulation: Solid block asphalt is crushed, dissolved in an organic solvent, and heated and stirred to obtain a homogeneous asphalt solution; the graphitized primary particles are mixed with the asphalt solution and dispersed to uniformly coat the surface of the graphitized primary particles, and then dried to obtain secondary particles. Carbonization: Under the protection of inert gas, the secondary particles are heated to 1000-1200℃ and kept at 1000-1200℃ for more than 2 hours to carbonize the asphalt on the surface of the secondary particles, followed by cooling, grinding and sieving.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The high-power lithium iron phosphate battery of the present invention optimizes the positive and negative electrode materials, including using ultrafine particles (median particle size of 0.2-2 μm) of transition metal-doped lithium iron phosphate cores combined with an ultrathin carbon layer (0.1-0.3 μm) to construct an efficient three-dimensional conductive network, reducing the electronic impedance of the positive electrode material, and using a soft carbon layer coated on the surface of graphite particles. Its porous structure and large specific surface area provide a fast channel for lithium ion insertion / extraction, reducing interface impedance. This enables the high-power lithium iron phosphate battery of the present invention to withstand higher charge and discharge currents. The synergistic effect of the two materials improves the high-power discharge capability of the battery.

[0017] The high-power lithium iron phosphate battery of this invention ensures the structural integrity of the electrodes during long-term cycling through the coating structure of the positive and negative electrode materials. By optimizing the electrolyte formulation and combining it with a separator coated with ceramic and polyvinylidene fluoride with high porosity, it is beneficial to form a stable and dense SEI film and CEI film on the positive and negative electrode surfaces, which significantly reduces the occurrence of side reactions and the consumption of active lithium during cycling. As a result, the high-power lithium iron phosphate battery of this invention can still maintain a capacity retention rate of more than 80% after 500 cycles of 1C charge / 10C discharge, and has a longer cycle life compared with conventional batteries.

[0018] The high-power lithium iron phosphate battery preparation method of this invention achieves a balance between high electrode loading and optimal capacity through precise slurry ratio and areal density control; ultrasonic welding is used to achieve low-damage, high-conductivity electrode tab welding, combined with laser welding to ensure the airtight seal of the battery casing and ensure battery safety; through a precise and controllable preparation process, high-quality and high-efficiency mass production of high-power lithium iron phosphate batteries is achieved, and the prepared high-power lithium iron phosphate batteries have high reliability, long cycle life and wide temperature range performance under high-power discharge.

[0019] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description

[0020] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof. In the drawings: Figure 1 This is a rate discharge curve of the lithium iron phosphate battery in Embodiment 1 of the present invention at 25°C; Figure 2 This is a discharge curve of the lithium iron phosphate battery in Embodiment 1 of the present invention at a constant power of 2000W at different temperatures; Figure 3 This is a cycle curve of the lithium iron phosphate battery in Embodiment 1 of the present invention, which is charged at 1C and discharged at 25°C. Detailed Implementation

[0021] To make the objectives and technical solutions of this invention clearer and easier to understand, the invention will be further described in detail below with reference to embodiments. The specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.

[0022] In the description of this invention, "several" means one or more, "more than" means two or more, "greater than," "less than," and "exceeding" are understood to exclude the stated number, while "above," "below," and "within" are understood to include the stated number. The use of "first" and "second" in the description is merely for distinguishing technical features and should not be construed as indicating or implying relative importance, or implicitly indicating the number of indicated technical features, or implicitly indicating the order of the indicated technical features.

[0023] Unless otherwise specified, the raw materials, reagents or devices used in the following examples are all available from conventional commercial sources or can be obtained by existing known methods.

[0024] In a first aspect, embodiments of the present invention provide a high-power lithium iron phosphate battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte; The positive electrode sheet includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The positive electrode material layer includes carbon-coated lithium iron phosphate positive electrode material, a conductive agent, and polyvinylidene fluoride (PVDF). The carbon-coated lithium iron phosphate positive electrode material consists of a transition metal-doped lithium iron phosphate core and a carbon layer coating the surface of the transition metal-doped lithium iron phosphate core. The transition metal is at least one of vanadium and titanium. The median particle size of the transition metal-doped lithium iron phosphate core is 0.2-2 μm. The carbon layer is obtained by solid-state sintering of at least one carbon source, glucose and sucrose, with at least one conductive material, graphene and carbon nanotubes, and has a thickness of 0.1-0.3 μm. The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The negative electrode material layer includes carbon-coated graphite negative electrode material, a conductive agent, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR). The carbon-coated graphite negative electrode material includes graphite particles and a soft carbon layer coated on the surface of the graphite particles. The median particle size of the graphite particles is 6-10 μm, and the soft carbon layer is obtained by pyrolysis of a liquid-phase carbon source and has a thickness of 0.2-1 μm. The diaphragm includes a base membrane and an adhesive layer composed of ceramic and polyvinylidene fluoride (PVDF) coated on the upper and lower surfaces of the base membrane. The base membrane is at least one of polypropylene and polyethylene, and the porosity of the diaphragm is 45% to 50%. The electrolyte comprises lithium salt, organic solvent and additives, wherein the mass ratio of lithium salt, organic solvent and additives is 13-18:75-80:3-8.

[0025] Specifically, high-rate discharge is achieved through optimization of the positive and negative electrode materials and structures; the stable coating structure of the positive and negative electrodes helps reduce the loss of active materials during charge-discharge cycles; at the same time, the optimized interface design forms a stable SEI film, enabling the lithium iron phosphate battery to have a long cycle life under high-power discharge; the separator adopts a dual coating of ceramic and polyvinylidene fluoride, providing excellent thermal stability and thermal shutdown protection, effectively preventing short circuits in the lithium iron phosphate battery and improving safety; the optimized electrolyte combined with a high-porosity separator ensures high-speed and smooth ion transport; through the synergistic optimization of the above aspects, high-power discharge performance, long cycle life, and high safety of the lithium iron phosphate battery are achieved.

[0026] Furthermore, the positive electrode uses an ultra-fine lithium iron phosphate core doped with transition metals, combined with an ultra-thin, highly conductive carbon layer, to improve the transport speed of lithium ions and electrons; the negative electrode uses soft carbon-coated graphite to reduce the resistance to lithium ion insertion / extraction, enabling rapid response to high-current charging and preventing lithium plating; the high porosity of the separator allows more electrolyte to be stored in it, effectively enhancing the separator's liquid retention capacity and ensuring the smooth flow of ion transport channels under high-power discharge; by optimizing the composition ratio of the electrolyte, the lithium salt concentration is kept at a high level to ensure a sufficient number of lithium ions for transport, while the addition of certain additives helps to form a low-impedance SEI / CEI film, ensuring that the lithium iron phosphate battery has both rapid ion migration under high-power discharge and performance degradation due to interface instability.

[0027] In some embodiments, the mass ratio of carbon-coated lithium iron phosphate cathode material, conductive agent, and polyvinylidene fluoride (PVDF) in the cathode material layer is 92-97:1-4:2-4.

[0028] Specifically, the high proportion of carbon-coated lithium iron phosphate cathode material in the positive electrode sheet is the core to achieving high energy density in high-power lithium iron phosphate batteries. By filling as much lithium iron phosphate material as possible within the limited electrode space to store and provide lithium ions, the capacity and range of high-power lithium iron phosphate batteries are guaranteed. The addition of conductive agents further constructs an efficient electrode conductive network, reduces electrode internal resistance, and improves rate discharge capability. The addition of binders helps to improve the structural integrity and electrochemical stability of the electrode, ensuring a long cycle life of the electrode.

[0029] In some embodiments, the positive current collector includes an aluminum foil and a carbon coating applied to the upper and lower surfaces of the aluminum foil. The carbon coating includes conductive carbon black, carbon nanotubes, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR), and the dry weight areal density of the carbon coating is 0.8-1.5 g / m³. 2 .

[0030] Specifically, by coating the positive electrode current collector with a carbon coating, a three-dimensional conductive network is constructed between the aluminum foil and the active material, reducing the interfacial contact resistance and improving the rate performance. At the same time, the carbon coating has a porous structure and a large specific surface area, which can form a strong mechanical engagement and physical adsorption with the positive electrode slurry, effectively preventing the positive electrode active material from peeling off from the positive electrode current collector during charge and discharge cycles, thereby affecting the long cycle life of high-power lithium iron phosphate batteries.

[0031] In some embodiments, the mass ratio of carbon-coated graphite anode material, conductive agent, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in the anode material layer is 92-97:0.5-2.5:1-2.5:1.5-3.

[0032] Specifically, the high proportion of carbon-coated graphite anode material in the negative electrode sheet can maximize the storage of lithium ions, which is the foundation for ensuring the high capacity and high energy density of high-power lithium iron phosphate batteries. The addition of conductive agents further constructs an efficient electrode conductive network, reduces the internal resistance of the electrode, and improves the rate discharge capability. The bonding system composed of sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) synergistically constructs a tough and stable electrode structure, enabling the negative electrode sheet to withstand the mechanical stress of long-term fast charging and discharging, thus achieving the long cycle life of high-power lithium iron phosphate batteries.

[0033] In some embodiments, the negative electrode current collector includes a copper foil and a carbon coating applied to the upper and lower surfaces of the copper foil. The carbon coating includes conductive carbon black and carbon nanotubes, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR). The dry weight areal density of the carbon coating is 0.5-1.2 g / m³. 2 .

[0034] Specifically, by coating the negative electrode current collector with a carbon coating, a three-dimensional conductive network is constructed between the copper foil and the active material, solving the problem of microscopic particle embedding on the surface of graphite particles, reducing interfacial contact resistance, and improving rate performance. At the same time, the carbon coating has a porous structure and a large specific surface area, which can form strong mechanical interlocking and physical adsorption with the negative electrode slurry, enhancing the structural stability of the negative electrode and contributing to the realization of long cycle life of high-power lithium iron phosphate batteries.

[0035] In some embodiments, the lithium salt in the electrolyte includes one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), lithium dioxolane borate (LiBOB), lithium tetrafluoroborate (LiBF4), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI); the organic solvent includes one or more of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethyl acetate (EA), and ethyl propionate (EP); and the additives include one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), lithium difluorooxolane borate (LiODFB), ethylene sulfate (DTD), tris(trimethylsilyl) phosphate (TMSP), and lithium difluorophosphate (LiPO2F2).

[0036] Specifically, the lithium salt is mainly lithium hexafluorophosphate (LiPF6), with the addition of one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), lithium dioxolane borate (LiBOB), lithium tetrafluoroborate (LiBF4), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), which helps to improve the conductivity and thermal stability of the electrolyte. The organic solvent is selected based on at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC), combined with ethyl acetate (EA) and ethyl propionate (EP) which have drag-reducing properties, to effectively optimize the low-temperature performance of high-power lithium iron phosphate batteries. The addition of additives works synergistically to enable the positive and negative electrodes to resist high temperature, high pressure and chemical corrosion, reduce electrolyte consumption, and effectively increase the cycle life of high-power lithium iron phosphate batteries.

[0037] In some embodiments, the high-power lithium iron phosphate battery further includes a cover plate and a connecting piece; the cover plate includes an electrode post with a diameter of 18-24 mm; the connecting piece includes a positive electrode connecting piece and a negative electrode connecting piece, the positive electrode connecting piece being an aluminum sheet with a thickness of 1.2-1.5 mm, and the negative electrode connecting piece being a copper or nickel sheet with a thickness of 0.8-1.2 mm.

[0038] Specifically, conventional electrode diameters are 14–16 mm. Using electrodes with a diameter of 18–24 mm increases current carrying capacity from 700A–1000A to over 1200A–2200A. Furthermore, the increased electrode area expands the BUSBAR welding area during PACK welding, mitigating the overheating issue of battery structural components during prolonged high-power discharge and improving the overall performance of high-power lithium iron phosphate batteries. Compared to traditional 0.8–1.0 mm thick aluminum connecting pieces, or 0.6–0.8 mm thick copper or nickel connecting pieces, the increased connecting piece thickness enhances the current carrying capacity between the tab and the cover plate, reduces heat generation in the structural component connecting pieces, and further improves the overall performance of high-power lithium iron phosphate batteries.

[0039] Secondly, embodiments of the present invention provide a method for preparing a high-power lithium iron phosphate battery, comprising the following steps: Preparation of the positive electrode: Carbon-coated lithium iron phosphate positive electrode material is prepared; the carbon-coated lithium iron phosphate positive electrode material, conductive agent, and polyvinylidene fluoride (PVDF) are mixed in an organic solvent at a mass ratio of 92-97:1-4:2-4 to form a uniform positive electrode slurry. The positive electrode slurry is then sized to have a dry weight areal density of 100-170 g / m³. 2 The coating is uniformly applied to the positive electrode current collector, and then dried, rolled, and sheared to obtain the positive electrode sheet. Preparation of the negative electrode sheet: Carbon-coated graphite negative electrode material is prepared. The carbon-coated graphite negative electrode material, conductive agent, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) are mixed in deionized water at a mass ratio of 92-97:0.5-2.5:1-2.5:1.5-3 to form a uniform negative electrode slurry. The negative electrode slurry is then prepared with a single-sided dry weight areal density of 50-80 g / m³. 2 The coating is uniformly applied to the negative electrode current collector, and then dried, rolled, and sheared to obtain the negative electrode sheet. Preparation of the diaphragm: The base membrane of the diaphragm is at least one of polypropylene and polyethylene, and an adhesive layer composed of ceramic and polyvinylidene fluoride (PVDF) is coated on the upper and lower surfaces of the base membrane to obtain a diaphragm with a porosity of 45% to 50%; wherein, the coating method includes one of multilayer coating, mixed coating and dot coating.

[0040] Preparation of electrolyte: Lithium salt, organic solvent and additives are mixed in a mass ratio of 13-18:75-80:3-8; Pre-processed battery assembly: The positive electrode sheet, separator, and negative electrode sheet are stacked and wound sequentially to form a battery cell; one end of the positive and negative electrode connecting pieces is connected to the positive and negative current collectors of the positive and negative electrode sheets using ultrasonic welding technology; the battery cell is placed in an aluminum shell and covered with a cover plate; the other end of the positive and negative electrode connecting pieces is connected to the positive and negative electrode posts of the cover plate using laser welding; the edge of the cover plate is sealed and welded to the edge of the opening of the aluminum shell; baking and drying are performed to obtain the pre-processed battery; Electrolyte injection, formation, sealing and Mylar film assembly: Inject electrolyte into the pre-processed battery casing and bake in an inert gas atmosphere for 8-15 hours; perform formation; seal the injection hole; heat shrink or fit the cut Mylar film onto the outside of the battery aluminum casing.

[0041] Specifically, through precise design of the electrode structure, low internal resistance of the electrodes and high power performance of high-power lithium iron phosphate batteries are achieved. By controlling the areal density of the positive and negative electrodes, the load and thickness of the electrodes are precisely controlled, ensuring the realization of high energy density and high capacity electrodes, which is beneficial to improving the safety performance and cycle life of high-power lithium iron phosphate batteries. Ultrasonic welding is used to connect the tabs to avoid high-temperature damage to materials, ensuring low resistance and high strength at the connection point, and enabling it to carry large currents. Laser welding is used for shell sealing, providing a permanent high-strength airtight seal to prevent moisture and air from entering, which is the foundation of long-term stability and safety. After electrolyte injection, a long baking time of 8 to 15 hours is performed to ensure that the electrolyte completely wets the electrodes and separator, avoiding local drying and preventing increased internal resistance and performance degradation. Through the formation process, a stable and dense SEI / CEI interface film is formed, effectively improving the first efficiency, cycle life and safety of high-power lithium iron phosphate batteries.

[0042] Furthermore, the conductive agent is selected from at least one of super carbon black (SP), carbon nanotubes (CNT), graphene, Ketjen black, vapor-grown carbon fiber (VGCF), and conductive graphite (KS-6).

[0043] In some embodiments, the preparation of carbon-coated lithium iron phosphate cathode material specifically includes the following steps: Lithium source, iron source, phosphorus source, vanadium source and titanium source were selected according to the molar ratio of ions Li + Fe 2+ :PO4 3- V 5+ Ti 4+ =1:1-xy:1:x:y is dissolved in deionized water or dispersed in ethanol, where 0 < x < 0.005 and 0 < y < 0.005; a carbon source and conductive material are added, dispersed to form a uniform slurry, and dried to obtain the precursor; The precursor is pre-sintered at 300-400℃ for 2-5 hours; The pre-sintered precursor is ground into a uniform powder, heated to 600-800℃ under inert gas protection, and held at 600-800℃ for 8-15 hours. After cooling, it is ground and sieved.

[0044] Specifically, lithium iron phosphate cores with a median particle size of 0.5~2μm are obtained through the above preparation method, and then coated with a 1~2μm carbon layer to form a dense conductive network, increasing the electronic conductivity of lithium iron phosphate. Simultaneously, vanadium and titanium are used to dope the iron sites of lithium iron phosphate, enhancing the lithium-ion diffusion rate and electronic conductivity of the cathode material. The electronic conductivity is increased from 10 times that of pure lithium iron phosphate. -10 ~10 ~9 S / cm increased to 10 -4 ~10 ~3 S / cm.

[0045] Furthermore, the lithium source is selected from at least one of lithium carbonate, lithium oxalate, lithium hydroxide, lithium acetate, and lithium nitrate; the iron source is selected from at least one of ferrous oxalate, ferrous acetate, ferric oxide, ferric phosphate, ferric nitrate, and ferric citrate; the phosphorus source is selected from at least one of phosphoric acid, ammonium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate; the vanadium source is selected from at least one of vanadium pentoxide and ammonium metavanadate; the titanium source is selected from at least one of titanium dioxide and tetramethyl titanate; the carbon source is selected from at least one of glucose and sucrose; and the conductive agent is selected from at least one of graphene and carbon nanotubes.

[0046] In some embodiments, the preparation of carbon-coated graphite anode materials specifically includes the following steps: Primary granulation: Select at least one of petroleum coke or needle coke, crush and shape it to obtain primary particles with a median particle size of 6-8μm; under inert gas protection, heat the primary particles to 2800-3000℃ and keep them at 2800-3000℃ for more than 3 hours to graphitize them, and obtain graphitized primary particles. Liquid phase carbonization coating and secondary granulation: Solid block asphalt is crushed, dissolved in an organic solvent, and heated and stirred to obtain a homogeneous asphalt solution; graphitized primary particles are mixed with the asphalt solution and dispersed to uniformly coat the surface of the graphitized primary particles, and then dried to obtain secondary particles. Carbonization: Under the protection of inert gas, the secondary particles are heated to 1000-1200℃ and kept at 1000-1200℃ for more than 2 hours to carbonize the asphalt on the surface of the secondary particles. Then, they are cooled, ground and sieved.

[0047] Specifically, primary particles with a median particle size of 6-8 μm are obtained through the above preparation method. Compared with large particle materials, primary particles with a median particle size of 6-8 μm have advantages such as high magnification and low expansion. By liquid-phase carbonization coating and secondary granulation of the primary particles, the coating layer is made more uniform, and the dynamic properties of the material are further enhanced to improve the magnification performance of graphite.

[0048] Preparation Example 1 Preparation of carbon-coated lithium iron phosphate cathode materials Lithium carbonate, ferrous oxalate, ammonium dihydrogen phosphate, ammonium metavanadate, and titanium dioxide were mixed in a molar ratio of Li ions. + Fe 2+ :PO4 3- V 5+ Ti 4+ Weigh the mixture in anhydrous ethanol at a ratio of 1:0.997:1:0.002:0.001 and disperse it in 80% of the total mass of the reactants. Add glucose and carbon nanotubes at a mass ratio of 1:2 to 48% of the mass of lithium carbonate. Ball mill the mixture for 4 hours to obtain a uniformly mixed slurry. Dry the slurry to obtain the precursor. Under nitrogen atmosphere protection, the precursor was heated to 400℃ at a rate of 2℃ / min for pre-sintering for 4 hours; The pre-sintered precursor was ground into a uniform powder and calcined at 700°C at a rate of 2°C / min under nitrogen atmosphere protection. The temperature was held for 10 hours and then cooled to room temperature. After grinding and sieving, carbon-coated lithium iron phosphate cathode material with a median particle size of 1.2±0.2μm was obtained.

[0049] Preparation Example 2 Preparation of carbon-coated graphite anode materials Petroleum coke with a carbon content of 98% was mechanically crushed and shaped to obtain primary particles with a median particle size of 7μm. Under nitrogen atmosphere protection, the primary particles were heated to 3000℃ and held at 3000℃ for 10 hours to obtain graphitized primary particles. Weigh 10% of the mass of the graphitized primary particles into solid block asphalt, crush it, dissolve it in tetrahydrofuran, and obtain a homogeneous asphalt solution by heating and stirring; add the graphitized primary particles, continue stirring and dispersing to make the asphalt evenly coat the surface of the graphitized primary particles, and dry to obtain secondary particles. Under nitrogen atmosphere protection, the secondary particles were heated to 1000℃, held for 4 hours, cooled to room temperature, and then ground and sieved to obtain carbon-coated graphite anode material with a median particle size of 8±0.5μm.

[0050] Preparation Example 3 Preparation of positive electrode current collector Prepare conductive carbon black, carbon nanotubes, CMC powder, and SBR emulsion in a mass ratio of 4:3:0.8:2.2. Add CMC powder to deionized water and stir until completely dissolved. Add conductive carbon black and stir to disperse evenly. Add carbon nanotubes and sonicate to ensure uniform dispersion. Add SBR emulsion while stirring and disperse evenly. Adjust the solid content to 18% with deionized water. Coat the coating on the upper and lower surfaces of aluminum foil using a microgravure coating process. The dry weight area density of the coating is 1.0 g / m³. 2 The positive current collector is obtained after cold pressing and compaction.

[0051] Preparation Example 4 Preparation of negative electrode current collector Prepare conductive carbon black, carbon nanotubes, CMC powder, and SBR emulsion in a mass ratio of 4:3:0.8:2.2. Add CMC powder to deionized water and stir until completely dissolved. Add conductive carbon black and stir to disperse evenly. Add carbon nanotubes and sonicate to ensure uniform dispersion. Add SBR emulsion while stirring and disperse evenly. Adjust the solid content to 18% with deionized water. Coat the coating on the upper and lower surfaces of copper foil using a microgravure coating process. The dry weight area density of the coating is 1.0 g / m³. 2 The negative electrode current collector is obtained after cold pressing and compaction.

[0052] Example 1 Preparation of the positive electrode: The carbon-coated lithium iron phosphate positive electrode material prepared in Preparation Example 1, super carbon black (SP), carbon nanotubes (CNTs), and polyvinylidene fluoride (PVDF) were mixed in N-methylpyrrolidone at a mass ratio of 95.5:1:1.5:2 to form a uniform positive electrode slurry. The positive electrode slurry was prepared with a dry weight areal density of 140 g / m³. 2 The positive electrode sheet is obtained by uniformly coating the positive electrode current collector prepared in Example 3, drying, rolling, and shearing. Preparation of the negative electrode: The carbon-coated graphite negative electrode material prepared in Preparation Example 2, super carbon black (SP), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water at a mass ratio of 94.7:1.5:1.5:2.3 to form a uniform negative electrode slurry. The negative electrode slurry was then weighed according to a dry weight surface density of 70 g / m³. 2 The anode material is uniformly coated onto the negative electrode current collector prepared in Example 4, and then dried, rolled, and sheared to obtain a negative electrode sheet. Preparation of the diaphragm: The base membrane of the diaphragm is a polyethylene membrane with a thickness of 9μm and a porosity of 55%. A slurry composed of nano-alumina and polyvinylidene fluoride is coated on the upper and lower surfaces of the base membrane by microgravure coating. After drying and compaction, a diaphragm with a total thickness of 12±1μm and an overall porosity of 48% is obtained. Preparation of electrolyte: LiPF6 and LiFSI are selected as lithium salts, EC, EMC and DMC are selected as organic solvents, and VC, FEC, DTD and TMSP are selected as additives. The mass ratio of lithium salts LiPF6 and LiFSI, organic solvents EC, EMC and DMC, additives VC, FEC, DTD and LiPO2F2 is 13:3.5:23.5:40:15.5:1:1:2:1. The organic solvents EC, EMC and DMC are mixed evenly, and then lithium salts LiPF6 and LiFSI and additives VC, FEC, DTD and LiPO2F2 are added and mixed evenly to obtain the electrolyte. Pre-processed battery assembly: A cover plate with a terminal diameter of 22mm is selected, a 1.5mm thick aluminum sheet is selected for the positive electrode connecting piece, and a 1.0mm thick nickel sheet is selected for the negative electrode connecting piece. The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in sequence to form a battery cell. Ultrasonic welding technology is used to connect one end of the positive and negative electrode connecting pieces to the positive and negative current collectors of the positive and negative electrode sheets respectively. The battery cell is placed in an aluminum shell and the cover plate is closed. The other end of the positive and negative electrode connecting pieces is connected to the positive and negative terminals of the cover plate respectively by laser welding. The edge of the cover plate is sealed and welded to the edge of the opening of the aluminum shell. After baking and drying, the pre-processed battery is obtained. Electrolyte injection, formation, sealing and Mylar film assembly: Inject electrolyte into the pre-processed battery casing and bake in an inert gas atmosphere for 8-15 hours; perform formation; seal the injection hole; heat shrink or fit the cut Mylar film onto the outside of the battery aluminum casing.

[0053] Example 2 Preparation of the positive electrode: The carbon-coated lithium iron phosphate positive electrode material prepared in Preparation Example 1, super carbon black (SP), carbon nanotubes (CNTs), and polyvinylidene fluoride (PVDF) were mixed in N-methylpyrrolidone at a mass ratio of 96:1.2:0.8:2 to form a uniform positive electrode slurry. The positive electrode slurry was prepared with a dry weight surface density of 150 g / m³. 2 The positive electrode sheet is obtained by uniformly coating the positive electrode current collector prepared in Example 3, drying, rolling, and shearing. Preparation of the negative electrode: The carbon-coated graphite negative electrode material prepared in Preparation Example 2, super carbon black (SP), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water at a mass ratio of 95:1.5:1.5:2 to form a uniform negative electrode slurry. The negative electrode slurry was then weighed to a dry weight surface density of 75 g / m³. 2 The anode material is uniformly coated onto the negative electrode current collector prepared in Example 4, and then dried, rolled, and sheared to obtain a negative electrode sheet. Preparation of the diaphragm: The base membrane of the diaphragm is a polyethylene membrane with a thickness of 9μm and a porosity of 55%. A slurry composed of nano-alumina and polyvinylidene fluoride is coated on the upper and lower surfaces of the base membrane by microgravure coating. After drying and compaction, a diaphragm with a total thickness of 12±1μm and an overall porosity of 48% is obtained. Electrolyte preparation: LiPF6 and LiFSI are selected as lithium salts, EC, EMC and DMC are selected as organic solvents, and VC, FEC, DTD and TMSP are selected as additives. The mass ratio of lithium salts LiPF6 and LiFSI, organic solvents EC, EMC and DMC, and additives VC, FEC, DTD and TMSP is 11:3.5:25.5:40:15.5:1:1:2:0.5. The organic solvents EC, EMC and DMC are mixed evenly, and then lithium salts LiPF6 and LiFSI and additives VC, FEC, DTD and TMSP are added and mixed evenly to obtain the electrolyte. Pre-processed battery assembly: A cover plate with a terminal diameter of 22mm is selected, a 1.5mm thick aluminum sheet is selected for the positive electrode connecting piece, and a 1.0mm thick nickel sheet is selected for the negative electrode connecting piece. The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in sequence to form a battery cell. Ultrasonic welding technology is used to connect one end of the positive and negative electrode connecting pieces to the positive and negative current collectors of the positive and negative electrode sheets respectively. The battery cell is placed in an aluminum shell and the cover plate is closed. The other end of the positive and negative electrode connecting pieces is connected to the positive and negative terminals of the cover plate respectively by laser welding. The edge of the cover plate is sealed and welded to the edge of the opening of the aluminum shell. After baking and drying, the pre-processed battery is obtained. Electrolyte injection, formation, sealing and Mylar film assembly: Inject electrolyte into the pre-processed battery casing and bake in an inert gas atmosphere for 8-15 hours; perform formation; seal the injection hole; heat shrink or fit the cut Mylar film onto the outside of the battery aluminum casing.

[0054] Example 3 Preparation of the positive electrode: The carbon-coated lithium iron phosphate positive electrode material prepared in Example 1, super carbon black (SP), carbon nanotubes (CNTs), and polyvinylidene fluoride (PVDF) were mixed in N-methylpyrrolidone at a mass ratio of 95:1.7:1.3:2 to form a uniform positive electrode slurry. The positive electrode slurry was measured to have a dry weight areal density of 136 g / m³. 2 The positive electrode sheet is obtained by uniformly coating the positive electrode current collector prepared in Example 3, drying, rolling, and shearing. Preparation of the negative electrode: The carbon-coated graphite negative electrode material prepared in Preparation Example 2, super carbon black (SP), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water at a mass ratio of 95:1.5:1.5:2 to form a uniform negative electrode slurry. The negative electrode slurry was measured to have a single-sided dry weight areal density of 70 g / m³. 2The anode material is uniformly coated onto the negative electrode current collector prepared in Example 4, and then dried, rolled, and sheared to obtain a negative electrode sheet. Preparation of the diaphragm: The base membrane of the diaphragm is a polyethylene membrane with a thickness of 9μm and a porosity of 55%. A slurry composed of nano-alumina and polyvinylidene fluoride is coated on the upper and lower surfaces of the base membrane by microgravure coating. After drying and compaction, a diaphragm with a total thickness of 12±1μm and an overall porosity of 48% is obtained. Preparation of electrolyte: LiPF6 and LiFSI are selected as lithium salts, EC, EMC and EA are selected as organic solvents, and VC, LiPO2F2, DTD and LIODFB are selected as additives. The mass ratio of lithium salts LiPF6 and LiFSI, organic solvents EC, EMC and EA, and additives VC, LiPO2F2, DTD and LIODFB is 7:7.5:20:18:42:2:1:2:0.5. The organic solvents EC, EMC and EA are mixed evenly, and then lithium salts LiPF6 and LiFSI and additives VC, LiPO2F2, DTD and LIODFB are added and mixed evenly to obtain the electrolyte. Pre-processed battery assembly: A cover plate with a terminal diameter of 22mm is selected, a 1.5mm thick aluminum sheet is selected for the positive electrode connecting piece, and a 1.0mm thick nickel sheet is selected for the negative electrode connecting piece. The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in sequence to form a battery cell. Ultrasonic welding technology is used to connect one end of the positive and negative electrode connecting pieces to the positive and negative current collectors of the positive and negative electrode sheets respectively. The battery cell is placed in an aluminum shell and the cover plate is closed. The other end of the positive and negative electrode connecting pieces is connected to the positive and negative terminals of the cover plate respectively by laser welding. The edge of the cover plate is sealed and welded to the edge of the opening of the aluminum shell. After baking and drying, the pre-processed battery is obtained. Electrolyte injection, formation, sealing and Mylar film assembly: Inject electrolyte into the pre-processed battery casing and bake in an inert gas atmosphere for 8-15 hours; perform formation; seal the injection hole; heat shrink or fit the cut Mylar film onto the outside of the battery aluminum casing.

[0055] The performance of the high-power lithium iron phosphate batteries prepared in Examples 1-3 was tested.

[0056] 1. Discharge capacity test (1) Test method 1. Nominal capacity (capacity at room temperature 1C) 1.1 Fully charge the battery at 25°C and let it stand at 25°C for 4 hours to ensure uniform temperature inside and outside the battery.

[0057] 1.2 Discharge to 2.0V at a constant current of 1C at 25℃, and record the discharge time.

[0058] 1.3 Calculation of nominal capacity at room temperature 1C: Capacity (Ah) = Discharge current (A) x Discharge time (h).

[0059] 2. Rate discharge capacity (3C, 5C, 7C, 10C) 2.1 Fully charge the battery at the test temperature and let it stand at the test temperature for 4 hours to ensure uniform temperature inside and outside the battery.

[0060] 2.2 Discharge to 2.0V at constant currents of 3C, 5C, 7C, and 10C at the test temperature, and record the discharge time.

[0061] 2.3 Calculation of discharge capacity at high rate: Capacity (Ah) = Discharge current (A) x Discharge time (h).

[0062] 3. Constant power discharge capacity (2000W discharge capacity) 3.1 Fully charge the battery at the test temperature (10℃, 25℃, 45℃, 60℃) and let it stand at the test temperature for 4 hours to ensure uniform temperature inside and outside the battery.

[0063] 3.2 Discharge the battery to 2.0V with the current required to maintain 2000W output, and record the discharge time.

[0064] 3.3 Calculation of 2000W discharge capacity: Capacity (Ah) = Discharge current (A) x Discharge time (h).

[0065] (2) Test results Table 1: Discharge capacity test results of Examples 1-3 2. Loop testing (1) Test method 1. Room temperature 1C charge / 10C discharge cycle test 1.1 Let the battery stand at 25°C for 4 hours to ensure uniform temperature inside and outside the battery.

[0066] 1.2 Charge at 25℃ with a constant current of 1C to 3.65V, then switch to constant voltage charging until the current drops to 0.05C, and let stand for 5 minutes.

[0067] 1.3 Discharge to 2.0V at a constant current of 10C at 25℃, let stand for 5 minutes; record the discharge capacity.

[0068] 1.4 Repeat steps 2.1.2 and 2.1.3 above until the set number of iterations.

[0069] 1.5 Calculation of Cyclic Capacity Retention Rate: Cyclic Capacity Retention Rate = Capacity after n cycles (Cn) / Capacity after the first cycle (C1).

[0070] (2) Test results Table 2: Cyclic Test Results of Examples 1-3 Through Table 1 and Figure 1 It can be seen that the high-power lithium iron phosphate battery of the present invention can still discharge normally at a high rate of 10C, and the voltage platform is stable. Even at a high rate of 10C discharge, the mid-terminal voltage can still be maintained above 3.0V, indicating that the high-power lithium iron phosphate battery of the present invention has low internal resistance and small polarization, which can meet the requirements of instantaneous high power output. As the discharge rate increases, the discharge capacity of the high-power lithium iron phosphate battery of the present invention remains above 80Ah, further indicating that the actual usable energy of the high-power lithium iron phosphate battery of the present invention does not decrease significantly due to high current, and has excellent performance in instantaneous high power output and long-term discharge.

[0071] Through Table 1 and Figure 2 It can be seen that the high-power lithium iron phosphate battery of the present invention exhibits stable performance within a wide temperature range of 10℃-60℃. Although the capacity decreases slightly at a low temperature of 10℃, it can still release most of its capacity without drastic voltage fluctuations, indicating excellent low-temperature adaptability. Examples 2 and 3, by adjusting the composition of the electrolyte and the ratio of each component, adapt the high-power lithium iron phosphate battery of the present invention to both high temperatures of 60℃ and low temperatures of 10℃. Example 2 demonstrates excellent performance at a high temperature of 60℃, with a 10C discharge capacity as high as 85.2Ah and a 2000W discharge capacity as high as 86.4Ah. Example 3 is adapted to a low temperature of 10℃, where its 10C discharge capacity is 80.6Ah and its 2000W discharge capacity is 81.1Ah, both remaining above 80Ah.

[0072] Through Table 2 and Figure 3 It can be seen that after 500 cycles of high-rate discharge (1C charge / 10C discharge) at room temperature, the capacity retention rate is still over 80%, and the capacity decay curve is relatively flat. This indicates that the active material and interface structure of the high-power lithium iron phosphate battery of the present invention are very stable during long-term cycling, which is beneficial to achieving a long cycle life for the high-power lithium iron phosphate battery. Examples 2 and 3, by adjusting the composition of the electrolyte and the ratio of each component, enable the high-power lithium iron phosphate battery of the present invention to be adapted to high temperatures of 60°C and low temperatures of 10°C, while maintaining room temperature cycle capacity retention rates of 83% and 85%, respectively. Although this is a decrease compared to 88% in Example 1, it is still at a high level of 80%.

[0073] In summary, the high-power lithium iron phosphate battery of the present invention, through optimization and adjustment of various aspects such as positive and negative electrodes, electrolyte, separator, and structural components, enables the prepared lithium iron phosphate battery to have high reliability, long cycle life, and wide temperature range under high-power discharge.

[0074] The above description is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made based on the content of the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A high-power lithium iron phosphate battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that, The positive electrode sheet includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The positive electrode material layer includes carbon-coated lithium iron phosphate positive electrode material, a conductive agent, and polyvinylidene fluoride (PVDF). The carbon-coated lithium iron phosphate positive electrode material consists of a transition metal-doped lithium iron phosphate core and a carbon layer coating the surface of the transition metal-doped lithium iron phosphate core. The transition metal is at least one of vanadium and titanium. The median particle size of the transition metal-doped lithium iron phosphate core is 0.2-2 μm. The carbon layer is obtained by solid-state sintering of at least one carbon source, glucose and sucrose, with at least one conductive material, graphene and carbon nanotubes, and has a thickness of 0.1-0.3 μm. The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The negative electrode material layer includes carbon-coated graphite negative electrode material, a conductive agent, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR). The carbon-coated graphite negative electrode material includes graphite particles and a soft carbon layer coated on the surface of the graphite particles. The median particle size of the graphite particles is 6-10 μm, and the soft carbon layer is obtained by pyrolysis of a liquid-phase carbon source and has a thickness of 0.2-1 μm. The diaphragm includes a base membrane and an adhesive layer composed of ceramic and polyvinylidene fluoride (PVDF) coated on the upper and lower surfaces of the base membrane. The base membrane is at least one of polypropylene and polyethylene, and the porosity of the diaphragm is 45% to 50%. The electrolyte comprises lithium salt, organic solvent and additives, wherein the mass ratio of the lithium salt, the organic solvent and the additives is 13-18:75-80:3-8.

2. The high-power lithium iron phosphate battery according to claim 1, characterized in that, In the cathode material layer, the mass ratio of the carbon-coated lithium iron phosphate cathode material, the conductive agent, and the polyvinylidene fluoride (PVDF) is 92-97:1-4:2-4.

3. The high-power lithium iron phosphate battery according to claim 1, characterized in that, The positive current collector comprises an aluminum foil and a carbon coating applied to the upper and lower surfaces of the aluminum foil. The carbon coating comprises conductive carbon black, carbon nanotubes, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR). The dry weight areal density of the carbon coating is 0.8-1.5 g / m³. 2 .

4. The high-power lithium iron phosphate battery according to claim 1, characterized in that, In the negative electrode material layer, the mass ratio of the carbon-coated graphite negative electrode material, the conductive agent, the sodium carboxymethyl cellulose (CMC), and the styrene-butadiene rubber (SBR) is 92-97:0.5-2.5:1-2.5:1.5-3.

5. The high-power lithium iron phosphate battery according to claim 1, characterized in that, The negative electrode current collector comprises a copper foil and a carbon coating applied to the upper and lower surfaces of the copper foil. The carbon coating comprises conductive carbon black and carbon nanotubes, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR). The dry weight areal density of the carbon coating is 0.5-1.2 g / m³. 2 .

6. The high-power lithium iron phosphate battery according to claim 1, characterized in that, In the electrolyte, the lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), lithium dioxolane borate (LiBOB), lithium tetrafluoroborate (LiBF4), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI); the organic solvent includes one or more of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethyl acetate (EA), and ethyl propionate (EP); the additives include one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), lithium difluorooxolane borate (LiODFB), ethylene sulfate (DTD), tris(trimethylsilyl)phosphate (TMSP), and lithium difluorophosphate (LiPO2F2).

7. The high-power lithium iron phosphate battery according to claim 1, characterized in that, The high-power lithium iron phosphate battery also includes a cover plate and connecting pieces; the cover plate includes an electrode post with a diameter of 18-24 mm; the connecting pieces include a positive electrode connecting piece and a negative electrode connecting piece, the positive electrode connecting piece being an aluminum sheet with a thickness of 1.2-1.5 mm, and the negative electrode connecting piece being a copper or nickel sheet with a thickness of 0.8-1.2 mm.

8. A method for preparing a high-power lithium iron phosphate battery, characterized in that, Includes the following steps: Preparation of the positive electrode: A carbon-coated lithium iron phosphate positive electrode material is prepared; the carbon-coated lithium iron phosphate positive electrode material, the conductive agent, and the polyvinylidene fluoride (PVDF) are mixed in an organic solvent at a mass ratio of 92-97:1-4:2-4 to form a uniform positive electrode slurry. The positive electrode slurry is then sized to have a single-sided dry weight areal density of 100-170 g / m³. 2 The material is uniformly coated onto the positive current collector, and then dried, rolled, and sheared to obtain the positive electrode sheet. Preparation of the negative electrode sheet: A carbon-coated graphite negative electrode material is prepared; the carbon-coated graphite negative electrode material, the conductive agent, the sodium carboxymethyl cellulose (CMC), and the styrene-butadiene rubber (SBR) are mixed in deionized water at a mass ratio of 92-97:0.5-2.5:1-2.5:1.5-3 to form a uniform negative electrode slurry. The negative electrode slurry is then prepared with a single-sided dry weight areal density of 50-80 g / m³. 2 The material is uniformly coated onto the negative electrode current collector, and then dried, rolled, and sheared to obtain the negative electrode sheet. Preparation of the diaphragm: The base membrane of the diaphragm is at least one of polypropylene and polyethylene. The upper and lower surfaces of the base membrane are coated with an adhesive layer composed of ceramic and polyvinylidene fluoride (PVDF) to obtain a diaphragm with a porosity of 45% to 50%. The coating method includes one of multilayer coating, mixed coating and dot coating. Preparation of electrolyte: The lithium salt, the organic solvent and the additive are mixed in a mass ratio of 13-18:75-80:3-8; Pre-processed battery assembly: The positive electrode sheet, the separator, and the negative electrode sheet are sequentially stacked and wound to form a battery cell; one end of the positive and negative electrode connecting pieces is connected to the positive and negative current collectors of the positive and negative electrode sheets using ultrasonic welding technology; the battery cell is placed in an aluminum shell and covered with a cover plate; the other end of the positive and negative electrode connecting pieces is connected to the positive and negative electrode posts of the cover plate using laser welding; the edge of the cover plate is sealed and welded to the edge of the opening of the aluminum shell; baking and drying are performed to obtain the pre-processed battery; Electrolyte injection, formation, sealing and Mylar film assembly: Inject the electrolyte into the casing of the pre-processed battery and bake it in an inert gas atmosphere for 8 to 15 hours; perform formation; seal the injection hole; heat shrink or fit the cut Mylar film onto the outside of the battery aluminum casing.

9. The preparation method according to claim 8, characterized in that, The preparation of carbon-coated lithium iron phosphate cathode material specifically includes the following steps: Lithium source, iron source, phosphorus source, vanadium source and titanium source were selected according to the molar ratio of ions Li + Fe 2+ :PO4 3- V 5+ Ti 4+ =1:1-xy:1:x:y is dissolved in deionized water or dispersed in ethanol, where 0 < x < 0.005 and 0 < y < 0.005; a carbon source and conductive material are added, dispersed to form a uniform slurry, and dried to obtain the precursor; The precursor is pre-sintered at 300-400℃ for 2-5 hours; The pre-sintered precursor is ground into a uniform powder, heated to 600-800℃ under inert gas protection, and held at 600-800℃ for 8-15 hours. After cooling, it is ground and sieved.

10. The preparation method according to claim 8, characterized in that, The preparation of the carbon-coated graphite anode material specifically includes the following steps: Primary granulation: Select at least one of petroleum coke or needle coke, crush and shape it to obtain primary particles with a median particle size of 6-8μm; under inert gas protection, heat the primary particles to 2800-3000℃ and keep them at 2800-3000℃ for more than 3 hours to graphitize them, and obtain graphitized primary particles. Liquid phase carbonization coating and secondary granulation: Solid block asphalt is crushed, dissolved in an organic solvent, and heated and stirred to obtain a homogeneous asphalt solution; the graphitized primary particles are mixed with the asphalt solution and dispersed to uniformly coat the surface of the graphitized primary particles, and then dried to obtain secondary particles. Carbonization: Under the protection of inert gas, the secondary particles are heated to 1000-1200℃ and kept at 1000-1200℃ for more than 2 hours to carbonize the asphalt on the surface of the secondary particles, followed by cooling, grinding and sieving.

Citation Information

Cited By

  • Battery monomer and preparation method thereof, battery device, power utilization device and energy storage device

    CN122246282A